Palliative care use amongst patients with bladder cancer. (12th March 2019) - Hugar, Lee A.; Lopa, Samia H.; Yabes, Jonathan G.; Yu, Justin A.; Turner, Robert M.; Fam, Mina M.; MacLeod, Liam C.; Davies, Benjamin J.; Smith, Angela B.; Jacobs, Bruce L.
Abstract : Objectives: To describe the rate and determinants of palliative care use amongst Medicare beneficiaries with bladder cancer and encourage a national dialogue on improving coordinated urological, oncological, and palliative care in patients with genitourinary malignancies. Patients and methods: Using Surveillance, Epidemiology, and End Results‐Medicare data, we identified patients diagnosed with muscle‐invasive bladder cancer (MIBC) between 2008 and 2013. Our primary outcome was receipt of palliative care, defined as the presence of a claim submitted by a Hospice and Palliative Medicine subspecialist. We examined determinants of palliative care use using logistic regression analysis. Results: Over the study period, 7303 patients were diagnosed with MIBC and 262 (3.6%) received palliative care. Of 2185 patients with advanced bladder cancer, defined as either T4, N +, or M + disease, 90 (4.1%) received palliative care. Most patients that received palliative care (>80%, >210/262) did so within 24 months of diagnosis. On multivariable analysis, patients receiving palliative care were more likely to be younger, female, have greater comorbidity, live in the central USA, and have undergone radical cystectomy as opposed to a bladder‐sparing approach. The adjusted probability of receiving palliative care did not significantly change over time. Conclusions: Palliative care provides a host of benefits for patients with cancer, including improved spirituality, decrease in disease‐specific symptoms, and better functional status. However, despite strong evidence for incorporating palliative care into standard oncological care, use in patients with bladder cancer is low at 4%. This study provides a conservative baseline estimate of current palliative care use and should serve as a foundation to further investigate physician‐, patient‐, and system‐level barriers to this care.